Evaluation of the artificial insemination programme for small-scale dairy farms in Malawi - Chagunda, Mizeck G.G.; Wollny, C.B.A.; Bruns, E.; Kamwanja, L.A. (1998)
The status of the artificial insemination (AI) program in Malawi was analysed exemplary in one of three small scale dairy farming regions. Data available from the Blantyre milk-shed area showed that the government controlled artificial insemination program applies a breed substitution strategy resulting in an increase of high grade Holstein-Friesian x Malawi Zebu crosses (>7/8 Friesian) from 388 in 1985 to 1228 cows in 1994. The semen is locally produced at the national AI center. Data for the estimation of breeding values of sires is not available. The annual number of inseminations per AI technician was very low (average 145 p.a.) suggesting low efficiency of the program. Logistics were the most significant constraint. The results suggest that the artificial insemination program for the small-scale farmers in Malawi requires a thorough revision. An inventory of the Malawi dairy cattle population and its genetic composition are recommended to provide basic information for the development of an appropriate breeding program. A cost efficient recording scheme is needed to provide meaningful data on the biological and economic efficiency of dairy cattle production in the small-scale sector in Malawi. The promotion of open locally based nucleus herds through participation of farmers and regular exchange of sires is recommended.